, Raseinių tanko" istorijos klausimu - Žardinskas, Arvydas (Lietuvos istorijos studijos, 2008)
During the opening days of the German-Soviet war in the area of Raseiniai, one of the largest tank battles took place. One episode of this battle is the so-called history of the tank of Raseiniai. This episode of the initial period of the war was researched by some historians, but almost all of them used the same sources. Therefore, we can find some misconstructions (e.g., that this panzer battle lasted two or even three days), and sometimes even solid authors make basic geographical mistakes. A heavy Soviet KV tank stopped on the way to Raseiniai - Šiluva and cut contact between two combat groups of the German 6th tank division for a whole day, holding up the fast advance of the German 41st motorized corps to the east. Attempts to destroy this tank with the new 50 mm anti-tank cannon, bombardment by large caliber cannon, and the use of engineers with explosives during the night all failed. An attempt to request air support also failed, as the Luftwaffe had other, more important targets. Only after delivering one more 88 mm cannon and with the help of an imitated tank attack did the Germans succeed in destroying the Soviet heavy tank. Describing the progression of the battle and establishing exact times and other facts became possible after reviewing archival documents (e.g., war diaries, radiograms) found in archives. But still, there are no answers to some questions. The author hopes that this study will help to uncover more about battles in the territory of Lithuania during the first week of the war on the Eastern Front.